Keabsahan Hukum Fitur Pengaduan Shopee Sebagai Bukti Elektronik dalam E-Commerce - Mardiyati, Nursanti (JURNAL USM LAW REVIEW, 2026)
This research aims to analyze the legal validity of Shopee’s complaint feature in Shopee transaction disputes and the legal implications if such evidence is not recognized in civil proceedings. The issue arises from disputes related to product discrepancies and the absence of clear legal standards regarding the admissibility of Shopee’s internal system records in civil litigation. The urgency of this research lies in ensuring legal certainty and consumer protection in e-commerce transactions. This study employs a normative juridical method with a statutory approach, supported by empirical data consisting of negative consumer reviews and documented cases of rejected refunds or returns on Shopee. The novelty of this research lies in its theoretical examination of Shopee’s complaint feature as admissible evidence under the Electronic Information and Transactions Law, the principle of legality in civil procedural law, and authentication as a prerequisite for the validity of digital evidence. The findings indicate that Shopee’s complaint feature meets the formal requirements of valid electronic evidence; however, in judicial practice, its evidentiary weight is often categorized merely as a supporting indication and considered weak due to authentication limitations, lack of digital forensic verification, non-transparent internal verification mechanisms, and inconsistent judicial acceptance in similar cases. This research contributes to the development of digital evidence assessment in e-commerce disputes by offering a framework for evaluating the validity of marketplace-based evidence. It further emphasizes the urgency of regulatory reconstruction and technical guidelines for the admissibility of digital evidence to ensure legal certainty, platform accountability, and consumer protection in online transactions. Penelitian ini bertujuan untuk menganalisis keabsahan hukum fitur pengaduan Shopee dalam kasus transaksi Shopee dan implikasi hukum jika fitur pengaduan tidak diakui sebagai bukti sah. Permasalahan ini berawal dari sengketa transaksi Shopee, terkait ketidaksesuaian barang dan ketiadaan standar hukum yang tegas dari sistem internal Shopee dalam proses perdata. Urgensi penelitian ini adalah untuk menjamin kepastian hukum dan perlindungan konsumen dalam transaksi e-commerce. Metode penelitian ini bersifat yuridis normatif dengan pendekatan perundang-undangan dan data empiris berupa ulasan negatif konsumen dan kasus penolakan refund atau retur Shopee. Kebaruan penelitian ini, secara teoretis menganalisis fitur pengaduan Shopee sebagai bukti yang sah menurut Undang-Undang Informasi dan Transaksi Elektronik asas legalitas pembuktian hukum acara perdata, dan konsep autentikasi sebagai syarat validitas bukti digital. Hasil penelitian menunjukkan bahwa fitur pengaduan Shopee memenuhi unsur sah alat bukti elektronik, namun dalam praktik peradilan kekuatan pembuktiannya dianggap sebagai petunjuk dan dipandang lemah karena keterbatasan autentikasi, verifikasi ahli digital forensik, tidak transparannya mekanisme verifikasi internal platform, serta inkonsistensi penerimaan oleh majelis hakim dalam perkara sejenis. Penelitian ini berkontribusi pada pengembangan kajian pembuktian digital dalam sengketa e-commerce dengan kerangka penilaian validitas bukti berbasis sistem marketplace. Penelitian ini menegaskan urgensi rekonstruksi regulasi dan pedoman teknis penerimaan bukti digital agar dapat menjamin kepastian hukum, akuntabilitas platform, dan perlindungan konsumen dalam transaksi daring.
Keywords: Bukti; Perlindungan Konsumen; Shopee